Quantitative analysis of cell distribution in injection molded microcellular foam. (May 2014) - Rizvi, SJA; Alaei, MH; Yadav, A; Bhatnagar, N
The microstructure of cellular materials, in particular microcellular polymers, is commonly characterized by the mean cell size and cell population density. Although the physical properties of foamed polymers are highly dependent on cell distribution, very insignificant work has been carried out to quantify the distribution of cells. This experimental study correlates the influential processing parameters of microcellular injection molding with the cell distribution, mean cell size and population density. For the first time, "Cell Distribution Index (CDI)", a quantitative parameter for characterization of foams has been defined in this paper. Foamed samples of polystyrene were prepared via microcellular injection molding process. The design of experiment includes five influential processing parameters (factors) at five different levels. Molded samples were fractured cryogenically and micrographs were obtained using a table top scanning electron microscope. With the help of image processing package, mean cell size, cell population density, frequency and newly defined term CDI were calculated for each micrograph. Finally, the effect of processing parameters on cell distribution was analyzed by plotting the CDI against the processing parameters.